HIV microarray for the mapping and characterization of HIV-specific antibody responses1. Issue 6 (21st March 2015) - Gallerano, Daniela; Wollmann, Eva; Lupinek, Christian; Schlederer, Thomas; Ebner, Daniel; Harwanegg, Christian; Niespodziana, Katarzyna; Schmetterer, Klaus; Pickl, Winfried; Puchhammer-Stöckl, Elisabeth; Sibanda, Elopy; Valenta, Rudolf
<x xml:space="preserve">Abstract</x> HIV microarray for the simultaneous measurement of antibodies towards a comprehensive set of HIV-derived peptides and proteins.